2015
DOI: 10.1152/japplphysiol.00662.2014
|View full text |Cite
|
Sign up to set email alerts
|

Acute dietary nitrate supplementation enhances compensatory vasodilation during hypoxic exercise in older adults

Abstract: We have previously demonstrated that aging reduces the compensatory vasodilator response during hypoxic exercise due to blunted nitric oxide (NO) signaling. Recent evidence suggests that NO bioavailability can be augmented by dietary nitrate through the nitrate-nitrite pathway. Thus we tested the hypothesis that acute dietary nitrate supplementation increases the compensatory vasodilator response to hypoxic exercise, particularly in older adults. Thirteen young (25 ± 1 yr) and 12 older (64 ± 2 yr) adults perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 67 publications
7
68
2
Order By: Relevance
“…Consistent with this, other approaches to potentiate the NO pathway (e.g. dietary nitrate) have been effective at improving exercise hyperemia in such populations (Casey et al 2015; Ferguson et al 2013). In addition, sildenafil citrate has been shown previously to increase resting forearm blood flow in conditions with impaired endothelial function such as smoking (Kimura et al 2003; Vlachopoulos et al 2004) and cardiovascular disease (Halcox et al 2002; Hryniewicz et al 2005; Schofield et al 2003).…”
Section: Discussionmentioning
confidence: 56%
“…Consistent with this, other approaches to potentiate the NO pathway (e.g. dietary nitrate) have been effective at improving exercise hyperemia in such populations (Casey et al 2015; Ferguson et al 2013). In addition, sildenafil citrate has been shown previously to increase resting forearm blood flow in conditions with impaired endothelial function such as smoking (Kimura et al 2003; Vlachopoulos et al 2004) and cardiovascular disease (Halcox et al 2002; Hryniewicz et al 2005; Schofield et al 2003).…”
Section: Discussionmentioning
confidence: 56%
“…An alternative explanation is that dietary nitrate supplementation does not alter any of the specific variables we measured involved with hypoxic acclimatisation; heart rate, blood pressure, SpO 2 , and ventilation rate. This is supported somewhat by Casey et al (23) who found no effect of nitrate supplementation on heart rate, blood pressure, and SPO 2 during very acute (<10 minutes) normobaric hypoxic exposure.…”
Section: Accepted Manuscriptmentioning
confidence: 64%
“…The main differences relate to the participants' age, and the length of hypoxic exposure. Firstly, we studied teenagers as opposed to adults, and the effect of dietary nitrate supplementation has been shown to improve skeletal muscle blood flow and vasodilation during hypoxic exercise in older individuals but not in younger people (23) . This suggests that the effect of nitrate supplementation on hypoxic adaptation may be age-dependent.…”
Section: Main Findingsmentioning
confidence: 99%
“…Interestingly, despite similar increases in plasma [NO 2 − ], NO 3 − supplementation significantly increased the vasodilation and blood flow response to hypoxic exercise in older participants (mean ± SD age 64 ± 2 years). The magnitude of the effect was such that age-related differences in compensatory vasodilation were abolished with NO 3 − supplementation, suggesting therapeutic utility of NO 3 − in older populations exercising in hypoxia [105] or potentially those afflicted with clinical conditions involving tissue hypoxia [106]. …”
Section: Physiological Effects Of Nitrate (No3−) Supplementation In Hmentioning
confidence: 99%